Karakter Nabi Ibrahim AS Dalam Al-Qur’an - Zaimudin Zaimudin (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
This paper emphasizes the significance of character for human beings as a result of the process of education and of social interaction with the its environments. These environments may be physical or non-physical, including the environment of family, neighbors and the environment of humans live. In addition, for Prophet Ibrâhîm as of course obtaining directions from God is more of a significant contribution in building the character of himself and his sons. This meaning is extracted from various verses of the Qur'an in a munasabah with an educational approachs. The characters of Prophet Ibrâhîm as in the Qur'an wich very useful for human beings these are: attitudes of obedient and submissive to God's command as a prerequisite for man to dedicate himself to his fellow human beings, his families, and to society at large on the basis of his devotion to God. The attitudes demand to dare to uphold truth and justice, to be brave in living and not afraid to fight for the right principles of life become very important. Being honest is a capital for moral development of the nation. Therefore, it is necessary to develop a attitude of caring towards themselves and their environment. Patience attitud is always needed to improve the situation, as well as polite speech and speech are important to build and understand the root causes of these conditions. It is also necessary to build a curiousity attitude in order to generate critical power and depth of knowledge, thoroughly and thoroughly without forgetting the meaning of ikhlas for the sake of the pleasure of Allah. The attitudes of praying and tawakkal always become important in achieving success in world and hereafter.